In vitro regeneration of black pepper (Piper nigrum L.) - Anny, Jong (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Black pepper (Piper nigrum L.) or known as King of spices, is an important cash crop of Malaysia and is widely used as food flavouring in the world. In vitro culture technique was introduced in mass production of black pepper for a newly released vaiety but, it is difficult to establish in vitro culture of black pepper due to the endophytic bacteria in pepper plant. Consequently, several measure are suggested in obtaining axenic culture of pepper.